Izglītība Latvijas PSR Kuldīgas apriņķī (rajonā): 1945–1956. - Gaile, Anna (Latvijas Universitāte, 2010)
Maģistra darba „Izglītība Latvijas PSR Kuldīgas apriņķī (rajonā): 1945–1956” mērķis ir izpētīt, kāda bija situācija izglītības jomā Kuldīgas apriņķī (rajonā) konkrētajā laika posmā. Darbā atspoguļota mācību iestāžu tīkla attīstība, materiālais nodrošinājums, obligātās izglītības realizācijas gaita. Novērtēta skolotāju loma oficiālo nostādņu un prasību kontekstā, atspoguļota kopējā situācija kadru jautājumā. Izpētīti mācību un audzināšanas darba uzdevumi, saturs un panākumi, komjaunatnes un pionieru organizāciju attīstība. Atsevišķi aplūkota vidējo izglītības iestāžu situācija un aktuālākās problēmas. Darbam ir novadpētnieciska ievirze, uzmanības centrā ir valsts realizētās izglītības politikas izpausmes Kuldīgas apriņķī (rajonā), tomēr pamatos tajā skarti visai Latvijas vēsturei nozīmīgi jautājumi. Tēma līdz šim nav pētīta.

The objective of the Master’s Paper Education in Kuldiga Region, Latvian SSR: 1945-1956 is finding out the situation in the field of education in Kuldiga Region over the given period of time. The Paper reflects upon issues like development of the network of educational institutions, material resources at their disposal, the course of implementation of the mandatory education system. The role of the teacher in the context of the official guidelines and requirements is analyzed and the overall situation in the field of personnel is described. The working tasks of training and upbringing, their substance and performance are studied, looking into the development of the Pioneer and Comsomol organizations. The status and most topical problems of secondary schools are separately in the Paper. The Paper is oriented on a local lore, it concentrates on manifestation of the state implemented education policy in Kuldiga Region, however it touches upon issues important for the history of Latvia as the whole. This theme has not been researched up to now.
Education in Latvian SSR Kuldiga’s district (region): 1946–1956.
Keywords: Vēsture